2011
DOI: 10.3138/jcfs.42.6.751
|View full text |Cite
|
Sign up to set email alerts
|

Post Migration Changes in Iranian Immigrants’ Couple Relationships in Canada

Abstract: Immigration presents a major life challenge, especially when the move is both geographical and across wide cultural divides. One of the areas of greatest challenge is in adjustments in gender and marital roles, perhaps because both of these are so close to the core of identity, self esteem, and sense of place in the world. This paper reports on research conducted with immigrants from Iran to Canada that examined how their experiences post-immigration affected their marital roles and relationship. Fifteen men a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Studies that have examined the persistence or renegotiation of gender roles in immigrant families provide additional insight into the challenges of competing cultural values after migration to a new society (e.g., Dasgupta, ; Hondagneu‐Sotelo, ; Parrado & Flippen, ; Shirpak, Maticka‐Tyndale, & Chinichian, ). Dasgupta () found that immigrant women feel conflicted between preserving the cultural traditions of their source countries and taking advantage of new opportunities available to them in the host country.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have examined the persistence or renegotiation of gender roles in immigrant families provide additional insight into the challenges of competing cultural values after migration to a new society (e.g., Dasgupta, ; Hondagneu‐Sotelo, ; Parrado & Flippen, ; Shirpak, Maticka‐Tyndale, & Chinichian, ). Dasgupta () found that immigrant women feel conflicted between preserving the cultural traditions of their source countries and taking advantage of new opportunities available to them in the host country.…”
Section: Introductionmentioning
confidence: 99%
“…These changes may not come easily (Hou, Neff, & Kim, ). For example, in a study of Iranian immigrants in Canada, men faced challenges adjusting to new gender roles and shifts in division of labor at home in response to women's labor force participation (Shirpak, Maticka‐Tyndale, & Chinichian, ).…”
Section: Family Formationmentioning
confidence: 99%
“…Immigration can present major life course challenges and changes in terms of gender roles within couples and families. For example, research conducted with Iranians in Canada examined how post-immigration experiences affected marital roles: men lost power and authority, whereas women experienced liberation from traditional patriarchal social systems (Shirpak et al 2011). Some men stated difficulty in accepting the freedom of wives to dress, socialize and make decisions for themselves in Canada.…”
Section: Migration and Changing Representations Of Gender Roles:-mentioning
confidence: 99%